2012
DOI: 10.1177/1089253212463969
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The Impact of Dexmedetomidine Infusion in Sparing Morphine Consumption in Off-Pump Coronary Artery Bypass Grafting

Abstract: Our study showed that dexmedetomidine might be an effective adjuvant in reducing both total hospital and intensive care unit length of stay in patients undergoing OPCAB. Dexmedetomidine might play a role in reducing total morphine and fentanyl consumption in OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…Indeed, 13 trials used dexmedetomidine in a general ICU setting [8], [12], [13], [26][29], [31][34], [37], ten in cardiac surgery ICU patients [7], [9], [10], [14], [15], [21], [24], [25], [30], [35], four in major non-cardiac surgery ICU patients [11], [22], [36], [38] and one after caesarean section-eclampsia admitted to ICU [23]. Different techniques of dexmedetomidine administration were used: in 18 trials the continuous infusion was preceded by a loading dose that was often 1 mcg/kg [13], [14], [17], [23], [24], [26], [28][30], [32], [33], [36] but that varied between 0.1 to 6 mcg/kg in other trials [11], [22], [25], [27], [30], [34], [37], [38]. In other 6 trials only continuous infusion was used and ranged between 0.1 to 2.5 mcg/kg/h [7][9], [15], [31], [35] while in one trial only the loading dose was used [10] and one trial gave no details [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 13 trials used dexmedetomidine in a general ICU setting [8], [12], [13], [26][29], [31][34], [37], ten in cardiac surgery ICU patients [7], [9], [10], [14], [15], [21], [24], [25], [30], [35], four in major non-cardiac surgery ICU patients [11], [22], [36], [38] and one after caesarean section-eclampsia admitted to ICU [23]. Different techniques of dexmedetomidine administration were used: in 18 trials the continuous infusion was preceded by a loading dose that was often 1 mcg/kg [13], [14], [17], [23], [24], [26], [28][30], [32], [33], [36] but that varied between 0.1 to 6 mcg/kg in other trials [11], [22], [25], [27], [30], [34], [37], [38]. In other 6 trials only continuous infusion was used and ranged between 0.1 to 2.5 mcg/kg/h [7][9], [15], [31], [35] while in one trial only the loading dose was used [10] and one trial gave no details [12].…”
Section: Resultsmentioning
confidence: 99%
“…Since several RCTs [7][14], including two large ones [8], were recently published, and one further RCT [15] was not included in the previous meta-analysis [6] we decided to perform an updated meta-analysis of all the RCTs ever performed on dexmedetomidine versus any comparator in the ICU setting to evaluate time to extubation, ICU stay and survival.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study from our laboratory (Junhui, Master's dissertation), it was found that the hemodynamics of patients at pump infusion of dexmedetomidine and tracheal intubation were relatively stable and ECG was not significantly changed (23,24). The study also showed that dexmedetomidine reduced the secretion of catecholamine before and after awake tracheal intubation, thereby effectively preventing the adverse stress reactions of the cardiovascular system during the intubation process but not significantly affecting the patients' respiration.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have suggested that using inhalational anesthetic agents for OPCAB might decrease myocardial injury and accelerate recovery of myocardial contractility (49,50). On the other hand, many different types of total intravenous (IV) anesthesia medication, including propofol, have been utilized for OPCAB surgery (48,(51)(52)(53). Lee and his associates (51) demonstrated that continuous IV infusion of lidocaine during OP-CAB surgery could reduce myocardial injury.…”
Section: Anesthetic Technique and Perioperative Challenges Of Opcabmentioning
confidence: 99%
“…Other studies have indicated that target-controlled infusion of remifentanil was superior to constant-rate infusion in suppressing the stress response during OPCAB and in maintaining the balance of the cardiac autonomic nervous system (52). One study also promoted the use dexmedetomidline as an adjunct therapy for patients undergoing OPCAB surgery; a selective α-2 agonist has been proven in reducing both total hospital and intensive care unit length of stay (53). Another study investigated propofol versus sevoflurane anesthesia, and demonstrated that propofol anesthesia was more beneficial to circulating T lymphocyte balance than sevoflurane anesthesia (54).…”
Section: Anesthetic Technique and Perioperative Challenges Of Opcabmentioning
confidence: 99%